Absurdo e censura na cena portuguesa: estudo do teatro de Prista Monteiro - Rodrigues, Márcia Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
After the end of World War II, portuguese theater refused the conventions of naturalism theater and started a renewal process of dramaturgy and scene. These Dramatic Art activities, however, were totally controlled by the censorship practiced by the dictatorial political regime (1926-1974), thus forcing playwrights and directors to quest for theatrical forms that could at the same time innovate the theatrical background and be approved by the censorship committee. By the end of the 1950's, the Brechtian epic theater and the theater of the absurd were the two main theatrical tendencies that interested portuguese playwrights. While the first one was sorely forbidden by the censors, the second one reached the stage since 1959, influencing the dramaturgical creations of new emerging playwrights. Among them was Helder Prista Monteiro (1922-1994) who had some of his plays presented during the dictatorial period and was considered by critics one of the exponents of the theatre of the absurd in Portugal. Considering the assumptions of the theater of the absurd, the relationship of that theater with censorship and the issues discussed by critics about the theatrical forms in vogue in the country, the theatrical work of Prista Monteiro constitutes the corpus of this thesis. Its main goal is to analise the plays written before the Carnation Revolution, with the intention of shedding a new light over the dramaturgy of this author and to prove that on it are reflected the attempts of a theatrical renewal along with the opposition to the political regime present on the time of its production

Depois do término da Segunda Guerra, o teatro português, tendo como meta a negação do naturalismo, inicia um processo de renovação da dramaturgia e da cena; no entanto, as atividades da arte dramática eram totalmente controladas pela censura imposta pelo regime político ditatorial (1926-1974), forçando dramaturgos e encenadores a buscar formas teatrais que fossem ao mesmo tempo inovadoras do panorama cênico e autorizadas pela censura. No final dos anos de 1950, o teatro épico-brechtiano e o teatro do absurdo constituíram as duas principais tendências teatrais que interessaram sobremaneira os dramaturgos portugueses; o primeiro foi intensamente interditado pela censura e o segundo alcançou os palcos a partir de 1959, influenciando a criação dramatúrgica dos novos autores que surgiam, dentre eles Helder Prista Monteiro (1922-1994), que teve algumas de suas peças encenadas durante a ditadura e foi considerado pela crítica um dos expoentes do teatro do absurdo em Portugal. Considerando os pressupostos do teatro do absurdo, as relações desse teatro com a censura e as questões discutidas no âmbito da crítica acerca das formas teatrais em voga no país, a obra dramática de Prista Monteiro constitui o corpus da presente tese, cujo principal objetivo é a análise das peças escritas antes da Revolução dos Cravos, com o intuito de lançar uma nova luz sobre a dramaturgia do autor e comprovar que nela estão refletidas as tentativas de renovação teatral e de objeção ao regime político vigente na altura de sua produção
Keywords: Monteiro, Helder Prista 1922-1994; Teatro; Teatro do absurdo; Censura; Dramaturgos; Dramatists